2020
DOI: 10.3389/fnhum.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

EEG Effective Source Projections Are More Bilaterally Symmetric in Infants Than in Adults

Abstract: Although anatomical brain hemispheric asymmetries have been clearly documented in the infant brain, findings concerning functional hemispheric specialization have been inconsistent. The present report aims to assess whether bilaterally symmetric synchronous activity between the two hemispheres is a characteristic of the infant brain. To asses cortical bilateral synchronicity, we used decomposition by independent component analysis (ICA) of high-density electroencephalographic (EEG) data collected in an auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…For example, we know that infant alpha activity projected onto central scalp electrodes is present only in later stages of infant development, presumably accompanying advances in motor skills ( Cuevas et al, 2014 ), although the sources of these scalp activations are yet to be identified. Further, at the source level, infant EEG is often more bilaterally symmetrical than adults ( Piazza et al, 2020 ), although strong topographical asymmetry or localisation to a specific topographical point can be a good indication of artifactual source components ( Chaumon et al, 2015 ). This evidence highlights that infant EEG source components do contain topographically distinct properties to those of typical adult EEG.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we know that infant alpha activity projected onto central scalp electrodes is present only in later stages of infant development, presumably accompanying advances in motor skills ( Cuevas et al, 2014 ), although the sources of these scalp activations are yet to be identified. Further, at the source level, infant EEG is often more bilaterally symmetrical than adults ( Piazza et al, 2020 ), although strong topographical asymmetry or localisation to a specific topographical point can be a good indication of artifactual source components ( Chaumon et al, 2015 ). This evidence highlights that infant EEG source components do contain topographically distinct properties to those of typical adult EEG.…”
Section: Introductionmentioning
confidence: 99%
“…Their localization can be estimated with an equivalent current dipole. In some cases, the SOBI components may correspond to a bilateral activation of homologous brain regions that can be modeled by symmetric dipoles (BĂŠnar et al, 2021; Piazza et al, 2020). We assumed the latter for the SOBI-MEG, representing a bilateral activation of the mesial network.…”
Section: Methodsmentioning
confidence: 99%
“…The electrophysiological functioning underlying auditory processing was explored by means of a non-speech multi-feature paradigm (extensively described previously [ 6 , 13 , 14 , 15 , 47 ]). In this paradigm, pairs of complex tones with an interstimulus interval (ISI) of 70 ms were presented.…”
Section: Methodsmentioning
confidence: 99%